Living With Multiple Myeloma: A Focus Group Study of Unmet Needs and Preferences for Survivorship Care. (March 2018) - Monterosso, Leanne; Taylor, Karen; Platt, Violet; Lobb, Elizabeth; Musiello, Toni; Bulsara, Caroline; Stratton, Kendall; Joske, David; Krishnasamy, Meinir
Purpose: To describe the unmet informational, psychological, emotional, social, practical, and physical needs and preferences for posttreatment survivorship care of individuals living with multiple myeloma to inform the development of relevant, person-centered, survivorship services. Methods: An exploratory, descriptive study using 2 focus groups with 14 participants, 6 to 49 months postdiagnosis. Results: Thematic analysis revealed 7 key themes: information needs, experience with health-care professionals, coping with side effects, communicating with family and friends, dealing with emotions, support needs, and living with the chronicity of myeloma. Participants described key characteristics of survivorship care relevant to their needs and indicated they would like a more whole of person approach to follow-up when the main treatment phases had completed. Conclusion: Participants in this study described unmet needs across a breadth of domains that varied over time. The development of flexible, person-centered approaches to comprehensive survivorship care is needed to address the considerable quality-of-life issues experienced by people living with multiple myeloma. Nurse-led care may offer 1 viable model to deliver enhanced patient experience—providing the vital "link" that people described as missing from their survivorship care.